Pengisian Jabatan Sekretaris Daerah di Sumatera Barat dalam Rangka Penerapan Sistem Merit - Ulya, Saufa Atika; Lubis, Khairani; Andora, Hengky (Universitas Ekasakti, 2023)
This study aims to find out how to fill the position of Regional Secretary in West Sumatra in the context of implementing the merit system. This research was conducted to find out how it was implemented and what factors influenced the Application of the Merit System in the Open Selection of Regional Secretaries in West Sumatra. The research method used is using a qualitative descriptive approach. In collecting data the author uses the interview method. The author performs data analysis by processing data, studying documents and drawing conclusions. The results of this study are to answer research questions related to the Filling of the Position of Regional Secretary in West Sumatra in the Context of Implementing the Merit System which is still not optimal. Even though the Government of West Sumatra has carried out all stages of the selection, be it the preparation, implementation, as well as monitoring and evaluation stages, in terms of compliance with the Application of the Merit System in the Open Selection of Regional Secretaries in West Sumatra, the implementation has not been optimal. This can be seen from several aspects that have not been implemented optimally. For optimal application of the Merit System, the Regional Government must already have competency standards for all positions, especially in filling the position of Regional Secretary.